One-step solid-state in-situ thermal polymerization of silicon-PEDOT nanocomposites for the application in lithium-ion battery anodes. (2nd September 2016) - McGraw, M.; Kolla, P.; Yao, B.; Cook, R.; Quiao, Q.; Wu, J.; Smirnova, A.
Abstract: The current study presents a one-step solid-state in-situ thermal polymerization approach to prepare silicon nanoparticles-polyethylenedioxythiophene (SiNPs-PEDOT) nanocomposites. The structure-related electrochemical performance of the in-situ polymerized 2, 5-dibromo-3, 4-ethylenedioxythiophene (DBEDOT) with SiNPs has been studied for the first time in application to silicon-based lithium-ion battery anodes. Thermal polymerization applied to a solution containing DBEDOT in acetonitrile with suspended silicon nanoparticles resulted in an in-situ formed SiNPs-PEDOT nanocomposite. The structure, morphology, and the corresponding electrochemical performance of the in-situ SiNPs-PEDOT nanocomposites was studied in comparison to a pure PEDOT as well as to the ex-situ polymerized SiNPs-PEDOT nanocomposites using XRD, FTIR, TGA, SEM, TEM, cyclic voltammetry, impedance spectroscopy, and constant current charge-discharge cycles. The XRD, FTIR, and TGA analysis reveal that the in-situ polymerization of monomer is not impeded by the presence of the silicon nanoparticles. The SEMand TEM studies reveal a uniform dispersion of SiNPs within in-situ polymerized PEDOT matrix compared to ex-situ formed SiNPs-PEDOT nanocomposite. In the lithium-ion battery anode, the in-situ polymerized SiNPs-PEDOT nanocomposite demonstrates the enhanced lithiation-delithiation kinetics, conductivity, and rate capability in comparison to the ex-situ SiNPs-PEDOT nanocomposite. Graphical abstract: Highlights: An in-situ thermal polymerization of DBEDOT with SiNPs was performed for the one-step fabrication of SiNPs-PEDOT electrode. The electrode of SiNPs-PEDOT nanocomposite on a Cu-support was studied for Li-ion battery anode application. The in-situ polymerization of monomer is not impeded by the presence of the SiNPs in SiNPs-PEDOT nanocomposite. The in-situ SiNPs-PEDOT electrode has better electrochemical performance in comparison to the ex-situ polymerized electrode.